The product for these two fractions is equal to 12/55
First you would divide 175 by 15 and get 11.6666666667, you would then multiply that by 18 amd get 210.0000000001
Answer:
10.7
Step-by-step explanation:
Answer:
B. (1,7)
Step-by-step explanation:
We can substitute the x and y values of each coordinate into the inequality and test if they work.
Let's start with A, 5 being y and 0 being x .
![5 > |0|+5\\5> 0+5\\5 > 5](https://tex.z-dn.net/?f=5%20%3E%20%7C0%7C%2B5%5C%5C5%3E%200%2B5%5C%5C5%20%3E%205)
5 IS NOT greater than 5, they are the exact same, so A is out.
Let's try B, 1 being x and 7 being y.
![7 > |1| + 5\\7 > 1 + 5\\7 > 6](https://tex.z-dn.net/?f=7%20%3E%20%7C1%7C%20%2B%205%5C%5C7%20%3E%201%20%2B%205%5C%5C7%20%3E%206)
7 IS greater than 6, so B. (1,7) does work for this inequality!
Let's do C for fun, when 7 is x and 1 is y.
![1 > |7| + 5\\1>7+5\\1>12](https://tex.z-dn.net/?f=1%20%3E%20%7C7%7C%20%2B%205%5C%5C1%3E7%2B5%5C%5C1%3E12)
1 IS NOT greater than 12, it is quite less than 12, so C doesn't work.
Therefore B. (1,7) works for the inequality of
.
Hope this helped!
Given:
A quadratic function has x-intercepts 2 and 6 and its vertex is (4, 8).
To find:
The corresponding quadratic expression.
Solution:
If graph of a function intersect the x-axis at c, then (x-c) is a factor of the function.
A quadratic function has x-intercepts 2 and 6. It means (x-2) and (x-6) are two factors of the required quadratic function.
The function is defined as:
...(i)
Where, a is a constant.
The vertex of the quadratic function is (4,8). It means the point (4,8) will satisfy the function.
Substituting x=4 and P(x)=8 in (i).
![8=a(4-2)(4-6)](https://tex.z-dn.net/?f=8%3Da%284-2%29%284-6%29)
![8=a(2)(-2)](https://tex.z-dn.net/?f=8%3Da%282%29%28-2%29)
![8=-4a](https://tex.z-dn.net/?f=8%3D-4a)
Divide both sides by -4.
![\dfrac{8}{-4}=a](https://tex.z-dn.net/?f=%5Cdfrac%7B8%7D%7B-4%7D%3Da)
![-2=a](https://tex.z-dn.net/?f=-2%3Da)
Putting
in (i), we get
![P(x)=-2(x-2)(x-6)](https://tex.z-dn.net/?f=P%28x%29%3D-2%28x-2%29%28x-6%29)
![P(x)=-2(x^2-6x-2x+12)](https://tex.z-dn.net/?f=P%28x%29%3D-2%28x%5E2-6x-2x%2B12%29)
![P(x)=-2(x^2-8x+12)](https://tex.z-dn.net/?f=P%28x%29%3D-2%28x%5E2-8x%2B12%29)
![P(x)=-2x^2+16x-24](https://tex.z-dn.net/?f=P%28x%29%3D-2x%5E2%2B16x-24)
Therefore, the correct option is B.